Удосконалений спосіб розріджування і оцукрювання замісів спиртового виробництва з використанням ультразвукового впливу - Маринченко, Віктор Опанасович; Носенко, Володимир Єрофійович; Маринченко, Лоліта Вікторівна (My University, 2013)
У статті експериментально обґрунтовано доцільність використання ультразвукового оброблення замісу з метою підвищення активності власних ферментів зерна амілолітичної, глюколітичної та протеолітичної дії та, відповідно, зменшення витрати ферментних препаратів на термофермен- тативну обробку й оцукрювання замісів у дослідних зразках на 30 %. За таких умов встановлено інтенсифікацію динаміки зброджування сусла на 6,6 %, збільшення глибини утилізації субстрату — на 0,17г/100 см3, підвищення виходу спирту — на 2,33 % об. порівняно з контролем. The advantage of the use of efficient commercial enzyme preparations in a progressive energy- and resource-saving technology thermo enzymatic treatment of batches is its high price, which leads to an increase in the cost of alcohol was determined. One possible way to intensify the activity of enzyme systems is to implement physical and chemical factors, such as the use of ultrasonic treatment while preparing raw materials to fermentation. The feasibility of using an ultrasonic treatment of mixing in order to increase the activity of its own grain enzymes of amylolytic and proteolytic activities and thus reduce fuel enzyme preparations on thermo enzymatic treatment and saccharification mixings in test samples by 30 % was investigated. Under these conditions it was founded that the dynamics of wort fermentation increased in 6.6 %; the depth of substrate utilization, in 0.17 g/100 cm3; and the alcohol yield, in 2.33 % of volume compared to the control samples.
Keywords: рохмалевмісна сировина; ультразвукове оброблення; заміс спиртового виробництва; зброджування; starch raw; mixing for alcohol; production; ultrasonic treatment; wort fermentation; кафедра біотехнології продуктів бродіння і виноробства; кафедра фізики та професійної безпеки